Development finance institutions: the need for bold action to invest better - Samantha Attridge; Matthew Gouett (Overseas Development Institute (ODI), 2021)
The United Nations Addis Ababa Action Agenda (AAAA) on financing development is at a critical juncture. It was off track before the Covid-19 pandemic struck and there is now a very real risk that it will veer even further off course without bold corrective action. Covid-19 has served to dramatically increase development needs, but development finance is under extreme pressure and at risk of decline. The Organisation for Economic Co-operation and Development (OECD) estimates that the Sustainable Development Goal (SDG) financing gap may balloon from 2.5 trillion to 4.2 trillion, with a 700 billion year-on-year reduction of private capital inflows to countries eligible for official development assistance (ODA) (OECD, 2020d). As policy-makers turn their attention to 'building back better' and mobilising the public and private resources required, there needs to be a clear understanding of why there has been so little progress in the past five years, with clear assessments of what has worked and what has not. To help inform new thinking, this report focuses on the mobilisation of private investment by development finance institutions (DFIs) and the private sector operations of multilateral development banks (MDBs). Private investment and a robust private sector are fundamental drivers of economic growth and job creation, which are key ingredients to help tackle poverty. DFIs and MDBs, with their core mandates to promote economic growth through investment, have been assigned a key role in supporting this agenda. The report seeks to inform and anchor the discussion by providing the most up-to-date analysis of DFI and MDB investment and the private finance this investment has mobilised in developing countries since 2013. It examines in detail the investment portfolios of 12 DFIs and MDBs who together mobilised more than 70% of the private finance reported to the OECD for the period 2017-2018. It reflects on four crucial issues: the Covid-19 crisis response; the relationship between ODA and DFI/MDB investment; DFI and MDB investment in low-income countries; and the need for greater transparency from DFIs and MDBs.
Keywords: 330; Entwicklungsfinanzierung; Entwicklungsbank; Entwicklungsländer; Welt